Digital Audit Evidence and Audit Independence: Evidence from the Big 4 Audit Firms in Nigeria - Kwarbai, Jerry Danjuma; Osunsusi, Akeem Kolawole; Ajayi-Owoeye, Ayooluwa Olotu; Olalere, Mayowa David; Ogunbiyi-Davies, Biodun Abiola; Aremu, Olabode Paul; Nwaobia , Apollos Nwabuisi (International Review of Management and Marketing, 2026)
This study examines the effect of digital audit evidence on audit independence among Big Four audit firms in Nigeria, with particular emphasis on analytical, forensic, electronic, and artificial intelligence–driven audit evidence. A survey research design was adopted. Data were collected from 365 employees of Big Four audit firms using a structured questionnaire. The data were analyzed using descriptive statistics and multiple regression analysis. The results reveal that digital audit evidence had significant positive effect on audit independence. Specifically, analytical procedural audit evidence, forensic audit evidence, and digital audit evidence gathering significantly enhance audit independence, while electronic documented audit evidence and AI-based confirmation evidence show insignificant effects. The study is limited to Big Four audit firms in Nigeria and relies on perceptual data. Future research may adopt longitudinal or experimental designs. Audit firms should prioritize investment in analytical and forensic digital tools and enhance auditor training in digital competencies to strengthen audit independence. The study contributes to the audit digitalization literature by disaggregating digital audit evidence into distinct components and providing evidence from an emerging economy.